Towards the X-shaped Person, the Next (Industrial) Leader in the Era of Industry 4.0 and Society 5.0 - Baskoro, Gembong (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2024)
This paper examines the impact on the development of industry and society known as industry 4.0 and society 5.0. Caused by technological and business pressures influenced by the rapid development of digital technology. Industry 4.0 and society 5.0 require the type of person who has digital literacy as well as leadership abilities to lead the industry in an uncertain market situation that can have an impact on disruption. Therefore, to ensure the sustainability of the industry, the type of person who is able to lead the industry through increasing business pressures and strategic environment is needed. This paper evaluates and assesses three shaped of person called I, T, and X on factors related to industrial sustainability, especially in the future due to industry 4.0. The assessment results show that X-shaped person has the highest score of 3.75 compared to I with a score of 1.31 and T with a score of 2.66. This result is specifically influenced by the leadership factor because it has the highest weighting factor of 0.34 for this assessment. This paper proposes an X-shaped person development method both through internal and external programs such as the Leadership Development Program (LDP) or government leadership program held by the National Resilience Institute of the Republic of Indonesia (Lemhannas RI). It is concluded that the X-shaped person is important to be developed for the sustainability and competitiveness of industry today and in the future.